The catechumenate in late antique Africa: Augustine of Hippo, his contemporaries and early reception (ca. 360-530 AD) - Pignot, M (2016)
In the late antique West, every individual becoming Christian first entered the community as a catechumen (catechumenus). Many spent several years in this status called the catechumenate, only ending with baptism and the acquisition of the membership of the faithful (fideles). This thesis considers the catechumenate not only as an initiation but as a peculiar way of being Christian. It demonstrates the fluid nature of Christian membership and shows how clerics strove to develop their authority over catechumens to build a cohesive community in a context of rivalry between churches and polemical controversies. The catechumenate both enabled converts to adhere progressively to the community and constituted an opportunity for clerics to set a standard path of progression, enforce discipline and define what it meant to be a Christian. This thesis opens up new avenues to study the process of Christianisation by stressing the continuous significance of the catechumenate for the formation of Christian communities in late antiquity. After an introduction, Chapter Two focuses on Augustine’s recollections of his time as a catechumen. Chapter Three looks at Augustine to investigate more broadly the practices of catechumeni, shedding light on the pervasive polemical context in which they are discussed. Chapter Four provides case studies on the cross put on the forehead to manifest Christian membership and the treatise De fide et operibus, exploring how Augustine aimed at shaping practices and ideas. Chapter Five investigates contemporary evidence: first an African canon regulating the ritual participation of catechumeni, then sermons describing unique rituals of the baptismal preparation and demonstrating that practices often varied locally. Chapter Six compares the sixth-century letter exchanges between Ferrandus and Fulgentius with John the Deacon’s letter to Senarius, showing the enduring importance of the catechumenate in the West and the creative reception of earlier African sources addressing recurrent pastoral problems.